Assessing the effectiveness of regional environmental quality management - E. I. Bobrova; I. V. Vyakina (Модернизация, инновация, развитие, 2024)
Purpose: is to present the author's modification of the methodology for assessing the effectiveness of regional environmental quality management, created on the basis of the approved regulatory, legal and methodological framework in the field of assessing the effectiveness of the activities of regional authorities.Methods: along with general scientific methods of information processing, comparative analogies and scientific generalization, analysis and synthesis, methods of content analysis of the regulatory framework, economic and statistical analysis, mathematical processing and visualization of data, as well as clustering techniques were used to unite regions into homogeneous groups that have common environmental quality characteristics.Results: the authors have performed the critical analysis of the methodology for calculating the indicator “Environmental Quality” within the framework of the approved regulatory and methodological framework in the field of assessing the effectiveness of the activities of regional authorities and identified its shortcomings; have developed proposals to eliminate them and modify the methodology. Based on publicly available information, a method for clustering regions by environmental quality was proposed and tested in the context of accepted determinants of environmental quality. The proposed modification of the methodology for assessing the effectiveness of regional management in terms of improving the calculation of the integral indicator “Environmental Quality” will improve the objectivity of assessing the quality of regional management of natural resources.Conclusions and Relevance: using the actual values of environmental quality indicators instead of indices of their dynamics and plan implementation will make it possible to cluster regions according to the proposed determinants of environmental quality. Comparison within a cluster of regions with similar natural and economic conditions will provide authorities with the opportunity to develop the natural resource management strategy and develop effective measures in the field of environmental management, taking into account the dynamics of the state of techno-natural systems.